Analysis of Volatile Flavor Compounds Differences in Organic and Non-organic Gonggan Mandarin Peel at Different Harvest Periods in Deqing County - Xiaoting ZHU; Gengsheng XIAO; Yuanshan YU; Jing WEN; Lina CHENG; Wenwen LIU; Yujuan XU; Manqin FU (Shipin gongye ke-ji)
To investigate the changes and differences in the volatile organic compounds (VOCs) of Deqing Gonggan Mandarin (GM) peels from organic (OGM) and non-organic (NGM) cultivation at different harvest periods, a comprehensive analysis of their VOCs was evaluated using fully automated colorimeter, electronic nose (E-nose), and headspace solid-phase microextraction combined with gas chromatography-mass spectrometry (HS-SPME-GC-MS). The results indicated that from September to January of the following year, the color of GM peel gradually shifted from green to yellow-red, and the OGM peel exhibited a brighter yellow hue. The HS-SPME-GC-MS analysis identified a total of 123 VOCs, predominantly consisting of terpenes, alcohols, aldehydes, esters and ketones. The analysis by E-nose and GC-MS revealed that the response values of W1W (sulfides and terpenes) and the mass concentration of terpenes (dominated by (+) limonene) were both highest and showed a significant increase month by month (P<0.05). With the same month, the mass concentration of terpenes in OGM peels was higher than in NGM peels. This indicated that the citrus aroma of the fruit peel intensified as the fruit matures, with OGM peels exhibiting a more pronounced citrus fragrance within each respective month. The peel samples collected at different harvest periods could be effectively categorized into green peel (from September to November) and yellow peel (from December to January of the following year). Compared with the green peel stage, the mass concentration of alcohols in the peel of GM was significantly lower in the yellow peel stage (P<0.05). OGM and NGM peel were screened for 18 and 15 differential VOCs (VIP>1), which were used to discriminate between peel samples from different harvest periods. Additionally, ten representative differential VOCs (P<0.05, VIP>1) were screened out, which could serve as aroma markers to distinguish between OGM and NGM peel samples.